Concreteness of thoughts and images during suppression and expression of worry. (December 2020) - Jendrusina, Alexander A.; Stevens, Elizabeth S.; Nahin, Erica R.; Legrand, Alison C.; Behar, Evelyn
Abstract: The avoidance theory of worry (Borkovec, Alcaine, & Behar, 2004) posits that the verbal-linguistic (versus imagery-based) nature of worry elicits abstract (versus concrete) processing, which inhibits affective responding and generates a host of negative consequences. Although suppression of worrisome thinking is maladaptive (Purdon, 1999), expression of worry using vivid imagery may increase concreteness of worrisome thinking and facilitate more adaptive emotional responding. The present study examined whether the valence, content, and expression of mentation impacts concreteness of thought. Participants ( N  = 62) were randomly assigned to verbalize their thoughts while engaging in either verbal-linguistic- or imagery-based mentation about both worrisome and neutral topics. Participants were also randomly assigned to engage in a 5-min period of suppressing or expressing the target stimuli before engaging in 5-min of freely expressing the targets. Verbalizations of mental content were coded for level of abstractness/concreteness. For neutral stimuli, imagery-based mentation led to greater concreteness than did verbal-linguistic mentation; however, for worrisome stimuli, imagery-based mentation did not enhance concreteness. In addition, for neutral (but not worrisome) stimuli, an initial period of suppression was associated with increased concreteness during subsequent expression. Imagery-based mentation about worrisome stimuli may not enhance concreteness; moreover, unlike suppression of neutral stimuli, suppression of worrisome stimuli may maintain, rather than ameliorate, abstractness of thought. Highlights: Examined concreteness of verbal vs imaginal mentation about worry vs neutral stimuli. Examined effects of expression vs suppression on concreteness of thought. For neutral stimuli, imagery led to greater concreteness of thought. For worrisome stimuli, imagery did not enhance concreteness. Suppressing neutral, but not worrisome, stimuli led to enhanced concreteness.